Правовая и социальная защищенность подчиненных как одно из основных направлений воспитательной работы офицеров - Nurulloyev, Laziz (Центр Научных Публикаций (buxdu.uz), 2021)
For th e last years th e situation in our society significantly exchanged th a t naturally influenced also activity of A rm ed Forces of ou r country. T he relevance of w ork is th a t the m ilitary p ersonnel needs social su p p o rt from th e state. It is necessary to u n d erstan d th at proceeding from a hum an factor, th e real efficiency of th e person involved in m ilitary activity directly depends on in w h at conditions he lives. R eadiness to give life for the H om eland has to be su p p o rted w ith th e real actions from th e state directed on creating favorable conditions for life of th e m ilitary and his family